Session report: Non-textbook type geomaterials - Giacheti, H. L. [UNESP] (My University, 2013)
An abstract of all the papers presented in the Conference Section where the geotechnical material is considered non-conventional to classical Soil Mechanics is presented. Thirteen papers submitted to this Conference were considered as a non-textbook type geomaterial. The papers were grouped in four groups: tropical soils, tailings, cementation and heterogeneous soils. The objective is to present a report with the major contributions of the each paper to encourage the reader to read the original papers. © 2013 Taylor & Francis Group.
Keywords: Cementation; Heterogeneous soils; Tailings; Tropical soils; Four-group; Geomaterials; Geotechnical material; Cementing (shafts); Characterization; Soil mechanics; Textbooks; Paper